External assurance of carbon disclosures indicates possible underestimates in reported European corporate emissions data - Georgios Papadopoulos (European Commission, 2023)
Company carbon disclosures are crucial in assessing a firm's impact on the environment, and many policy actions are associated with this information. As a response to the rising demand for transparency and related regulatory requirements, an increasing number of firms discloses information on their greenhouse-gas (GHG) emissions and voluntarily engage with external assurance of the reported information. However, the possible existence of systematic differences in reported emissions with respect to their assurance status is still underexplored. This study investigates the causal effect of third-party assurance on carbon disclosures in a sample of European companies. Findings suggest that non-assuring firms may be under-reporting their direct GHG emissions by up to a magnitude comparable to the largest annual reduction of EU emissions in history. On the contrary, the effect of assurance is much weaker to almost absent in indirect, Scope 2, emissions possibly due to their clear and easily verifiable estimation nature. These findings demonstrate that third-party assurance can provide more reliable and certainly more prudent estimates of corporate GHG emissions which are relevant to corporate sustainability strategy, policymaking and, ultimately, climate change mitigation.
Keywords: 330; external assurance; corporate carbon disclosure; company GHG emissions; climate change